Analisis Faktor-faktor yang Mempengaruhi Audit Delay dan Timeliness pada Perusahaan Publik di Indonesia (Studi Empiris pada Perusahaan yang Terdaftar Secara Konsisten di LQ45 pada Bursa Efek Indonesia) - Baradha Pratama; Santosa Adiwibowo (Diponegoro Journal of Accounting, 2014)
The aim of this research is to analyze the effect of profitability, company size, solvability rate,industry classification, and size of public accounting firm to audit delay and timeliness of the go public company that listed as LQ45 in Indonesian Stock Exchange in the years of 2009-2012. There are seven variables in this research that consist of five independent variables namely profitability, firm size, solvability rate, industry classification, and size of public accounting firm and two dependent variables namely audit delay dan timeliness. The method of sample selection in this researc using purposive sampling method which consist of 24 companies that consistenly listed as LQ45 in Indonesian Stock Exchange in the periode of 2010-2013 were consistenly submitted financial statement for 2009-2012. The analysis tool that used in this research is multiple regression. According to the results of research, it can be concluded that audit delay affected by company size, solvability rate, and industry classification. While timeliness is affected by industry classification and solvability rate.